Multidimensional Approach of Genotype and Phenotype in Stroke Etiology: The MAGPIE Study - Redoy Ranjan; Dipannita Adhikary; Shanto Barman; Md. Shuktarul Islam; Gie Ken‐Dror; Md. Abdullah Yusuf; Adneen Moureen; Maliha Hakim; Pankaj Sharma (Health Science Reports, 2024)
ABSTRACT Background and Aims Stroke is a leading cause of mortality and morbidity in Bangladesh. It is estimated that genetic determinants account for around 40%–60% of its etiology, similar to environmental factors. This study aimed to provide a better understanding of the genetic, environmental, and clinical risk factors in stroke patients from Bangladesh. Methods The MAGPIE (Multidimensional Approach of Genotype and Phenotype In Stroke Etiology) study is a population‐based case‐control study that will allow a hypothesis‐free genome‐wide association study (GWAS) to identify genetic risk factors associated with adult stroke (age ≥ 18 years) in Bangladesh. This study will collect detailed phenotypic data as well as blood samples from stroke patients and control subjects. High‐molecular‐weight genomic DNA will be isolated and archived using Qiagen DNA isolation kits. Results We will utilize SPSS v28.0, vR‐4.3.2 and gPLINK v2.0 software to analyse the study variables, as appropriate. Further, appropriate statistical tests will be applied to test the significance level between study groups. As applicable, data will be presented in tables and graphs, such as Manhattan plots and Quantile‐Quantile (QQ) plots. A p < 0.05 will be considered as statistical significance. Conclusion This will be the first large‐scale carefully phenotyped biobank of Bangladeshi stroke patients which will enable a GWAS enabling an understanding of the association between gene‐phenotype risk factors which has the potential to revise and refine national stroke guidelines.